Create A 3D Map From The Old Town Of Lopburi Province On Mobile. - et. al., Duangthip Rubporndee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Research in creating a three-dimensional model for tourist attractions in the Old Town, Lop Buri Province, which has data sources from the Lop Buri Old Town Tourism Information Book. It was divided by age according to the era of the various places, and solved by creating three-dimensional models which was a research method with the objective of 1) to build an archaeological site that is the main point in all three dimensions according to the era, 2) to create a tourist map of the Old City in Lop Buri Province in a three-dimensional model, 3) to assess the satisfaction of users of the Old Town Tourism Map in Lop Buri Province, and 4) to transfer technology to interested parties or interested agencies which began by bringing information from books and analyze concepts for use in event planning. It consisted of collecting data in a multi-angle, horizontal real-time shooting for creating historic sites in a three-dimensional model to import into a two-dimensional tourist map model. Target group are interested parties and 80 tourists. Research findings showed that the overall satisfaction level was at a high level. The overall average score was 4.29, the standard deviation was 0.678. When analyzed in each aspect, it found that the highest score was at the technical level with an average score of 4.73, the standard deviation of 0.458, with the highest level of satisfaction.